Optimal placement of distributed generation in distribution network: a review on hybrid techniques / Nur Atiqah Abdul Rahman, Zulkiffli Abdul Hamid and Nur Ashida Salim - Abdul Rahman, Nur Atiqah; Abdul Hamid, Zulkiffli; Salim, Nur Ashida (UiTM Press, 2024)
The integration of DG provides many benefits to the distribution system. To integrate DG, a proper location and size need to be taken into consideration. Poor planning of DG integration may lead to severe impact to the power system. Therefore, the proper technique is required to find the optimal location and size of DG to ensure the distribution system can deliver a reliable power supply to the consumers. Throughout the years, there have been a lot of techniques being proposed to optimally allocate DG into the distribution network considering various objectives. From conventional techniques to metaheuristic techniques and hybrid techniques, all of them can provide optimal location of DG to solve either single objective or multi-objective functions. However, hybrid techniques now have become more attractive to researchers as it gives better performance and can eliminate some of the drawbacks available in conventional and metaheuristic techniques when working individually. Thus, this paper presents a review on Hybrid Techniques for Optimal Placement of Distributed Generation in Distribution Network. In this paper some of the hybrid techniques available in the past and recent literature were reviewed by focusing on how the technique can provide optimal location and sizing of DG to solve various objective functions such as minimizing power losses, improving voltage stability and reliability in power system. A summary of hybrid techniques is also presented in this paper. The review shows that the hybrid techniques provide better performance compared to conventional techniques available in the literature.